2017
DOI: 10.1016/j.worlddev.2017.05.020
|View full text |Cite
|
Sign up to set email alerts
|

The Livelihood Impacts of Cash Transfers in Sub-Saharan Africa: Beneficiary Perspectives from Six Countries

Abstract: Social characteristics Gender, age, disability, etc. of household members within lifecycle of domestic group Assets Capability Multi-dimensional vulnerability Shaped by CT impact pathways Alleviation of credit, liquidity & savings constraints Access to risk sharing networks for economic collaboration, labour, technology, knowledge, inputs VULNERABILITY CONTEXT Multivariate risks creating stresses, shocks, trends, cycles that effect beneficiary households Household Income Consumption, nutrition Investment in ed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
62
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 87 publications
(70 citation statements)
references
References 22 publications
(30 reference statements)
4
62
0
Order By: Relevance
“…In this respect, cash transfers, such as through the HSNP, may act as better social protection for the poorest households, and with asset‐building capacity (Fisher et al., ). Comparison between IBLI and HSNP leads Jensen, Barrett, and Mude () to conclude that beneficial impacts flow from both programmes; they do, however, highlight how their different cost structures mean that IBLI's impact per unit cost are higher than HSNP's.…”
Section: Index Insurance Through the Lens Of Social Equitymentioning
confidence: 99%
See 1 more Smart Citation
“…In this respect, cash transfers, such as through the HSNP, may act as better social protection for the poorest households, and with asset‐building capacity (Fisher et al., ). Comparison between IBLI and HSNP leads Jensen, Barrett, and Mude () to conclude that beneficial impacts flow from both programmes; they do, however, highlight how their different cost structures mean that IBLI's impact per unit cost are higher than HSNP's.…”
Section: Index Insurance Through the Lens Of Social Equitymentioning
confidence: 99%
“…It is of least benefit to the poorest with meagre asset endowments where drought leads to herd collapse (<10 TLU; 26% of the population); and not so vital for wealthier pastoralists (27% of the population). T A B L E 2 (Continued) In this respect, cash transfers, such as through the HSNP, may act as better social protection for the poorest households, and with asset-building capacity (Fisher et al, 2017). Comparison between IBLI and HSNP leads Jensen, Barrett, and Mude (2014) to conclude that beneficial impacts flow from both programmes; they do, however, highlight how their different cost structures mean that IBLI's impact per unit cost are higher than HSNP's.…”
Section: Equitable Access Procedures Representation and Outcomesmentioning
confidence: 99%
“…In addition to increase welfare, livelihood improvement interventions with effective program implementation is needed, while regional policies which expand the opportunity space are needed to support the development and improvement of innovation systems to accelerate the creation of youth that can lead variety of agricultural employment activities (Fisher et al, 2017;Jiao, Pouliot, & Walelign, 2017;Kararach, Hanson, & Léautier, 2012;Martin & Lorenzen, 2016;Steenbergen, Marlessy, & Holle, 2017). Perceptions on individual household income express that the most participating young people considered higher production and intensiveness of harvesting (Oyedele & Adenegan, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Previous analysis examining the impacts of the Social Cash Transfer Program (SCTP) and Multiple Category Targeted Grant (MCTG) on primary outcomes has concluded that at the household level, both programs increased consumption, food security, material welfare and assets, and strengthened livelihoods and productive investment, while decreasing monetary poverty (UNC ; Fisher et al. ; Brugh et al. ; Handa et al.…”
mentioning
confidence: 99%
“…Previous analysis examining the impacts of the Social Cash Transfer Program (SCTP) and Multiple Category Targeted Grant (MCTG) on primary outcomes has concluded that at the household level, both programs increased consumption, food security, material welfare and assets, and strengthened livelihoods and productive investment, while decreasing monetary poverty (UNC 2016;Fisher et al 2017;Brugh et al 2018;). In addition, both programs were found to increase child school attendance, yet non-negligible increases were also found in child work participation (both in household entrepreneurial activities and household chores) as children played a role in helping with household productive investment (de Hoop, Groppo, and Handa 2017;Kilburn et al 2017).…”
mentioning
confidence: 99%